STRATEGI PENGELOLAAN KELAS INOVATIF TERHADAP PENGURANGAN KETIMPANGAN LITERASI BERBANTUAN TEKNOLOGI DIGITAL SISWA KELAS 1 SD - Azkiya, Azza; Rukmawati, Rukmawati (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to explain classroom management strategies implemented to reduce literacy inequality among first-grade students at SD Negeri Munggangsari. Literacy inequality remains a serious problem at the elementary school level, primarily due to differences in learning motivation, access to reading materials, and support from the learning environment. This study used a descriptive qualitative approach and collected data through semi-structured interviews with teachers and observations of classroom learning processes. The study findings revealed that the main strategy implemented by teachers was providing rewards, such as praise, stickers, and positions as "Reading Leaders" for students who showed progress or active engagement in reading activities. This method proved effective in increasing student motivation and interest, as well as building a supportive and collaborative classroom atmosphere. The data obtained showed a very significant decrease in the number of students with low literacy levels from 42% to 19%, as well as an increase in the number of students with medium and high literacy levels. The conclusion of this study is that a reward-based classroom management method can significantly reduce literacy inequality among students. This method is recommended to be implemented routinely in the early grades of elementary schools, with training support for teachers and the provision of adequate literacy facilities.